Quasispecies dynamics on a network of interacting genotypes and idiotypes: applications to autoimmunity and immunodeficiency. (29th June 2016) - Barbosa, Valmir C; Donangelo, Raul; Souza, Sergio R
Abstract: In spite of their many facets, the phenomena of autoimmunity and immunodeficiency seem to be related to each other through the subtle links connecting the mutation and action of retroviruses (viruses whose genetic material can find its way into that of the host's cells and destroy them) to immune response and adaptation. In a previous work, we introduced a network model of how a set of interrelated genotypes (called a quasispecies, in the stationary state, representing for example a population of viruses) and a set of interrelated idiotypes (an idiotypic network, representing the immune system through its population of B and T cells) interact. That model, which does not cover the case of a retroviral quasispecies, is here extended by the addition of a further parameter ( ν ) to account for the action of retroviruses (i.e. the destruction of idiotypes by genotypes). We give simulation results within a suitable parameter niche, highlighting the issues of quasispecies survival and of the onset of autoimmunity through the appearance of the so-called pathogenic idiotypes (those that mimic some external pathogen). Our main findings refer to how ν and λ, a parameter describing the rate at which idiotypes get stimulated, relate to each other. While for ν > λ the quasispecies survives at the expense of weakening the immune system significantly or even destroying it, for ν < λ the fittest genotypes of the quasispecies become mimicked inside the immune system as pathogenic idiotypes. The latter is in agreement with the current understanding of the HIV quasispecies.